Patterns for Settlement of Punah Inheritance Disputes In the Community of Nagari Salareh Aia from the Perspective of Islamic Law - Elfia; Sandria Milka Ratna Sari; Ikhwan; Muchlis Bahar; Nurus Shalihin (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This research aims to investigate the settlement pattern of inheritance disputes in Nagari Salareh Aia as well as the impact of this settlement pattern. This is a field study using customary law and Islamic law approaches. Data were obtained through interviews and document studies. To analyze data, the Creswell approach was used, which includes data reduction, data verification, and drawing conclusion. This research reveals three significant findings. First, the customary settlement pattern, for heirs who control punah inheritance, is done by selling it to other. If there are one or more heirs, the remaining sale of the assets is divided among the heirs after the Mamak's rights are excluded. Second, the settlement of punah inheritance disputes in Salareh Aia fosters close family ties. It also clarifies the heirs' position regarding inheritance and property status, whether it is a high inheritance or low inheritance. Third, based on the pattern of settlement and the resulting impact, it can be concluded that the mechanism for resolving disputes over the Punah inheritance in the Nagari Salareh Aia has fulfilled sharia principles, namely to maintain the property and the honor of the people.